STUDENT COMMUNICATION IN NUMERIC LITERATIONS USING CANADIAN MULTIPLICATION MEDIA - Martin Indah; Tundung Memolo (Yayasan Citra Dharma Cindekia, 2020)
The purpose of this study was to determine the extent to which students' communication skills on numerical literacy in multiplying two numbers using Canadian Multiplication media. This research method is descriptive research. From the planning, implementation, and reporting stages it is carried out for 3 months. Starting from the beginning of August to the second Sunday of November 2017. The implementation of this research was conducted with the subject of second grade students of SD Negeri Medalem Kec. Modo Kab. Lamongan, amounting to 3 students on Wednesday, November 8, 2017. Result the average communication ability of students is 79.2% while the average numerical literacy ability of grade 2 SD Negeri Medalem Kec. Modo Kab. Lamongan in the competency of multiplying two numbers shows 86.7%. Canadian Multiplication Media is an effort as a form of teacher innovation in learning to develop student communication through numerical literacy activities.